Role of pentose phosphate pathway in lipid accumulation of oleaginous fungus Mucor circinelloides. Issue 118 (17th November 2015) - Zhao, Lina; Tang, Xin; Luan, Xiao; Chen, Haiqin; Chen, Yong Q.; Chen, Wei; Song, Yuanda; Ratledge, Colin
Abstract : Overexpressing the genes coding for glucose 6-phosphate dehydrogenase and 6-phosphogluconate dehydrogenase from the pentose phosphate pathway in the oleaginous fungus Mucor circinelloides increased the lipid content of cell dry weight by 20–30%. Abstract : Lipid biosynthesis in oleaginous fungi requires acetyl-CoA, as the essential precursor of fatty acids, and a supply of reducing power, NADPH. Malic enzyme provides the majority of NADPH needed for lipid biosynthesis in most oleaginous fungi, while the reactions of the pentose phosphate pathway (PPP) provide additional NADPH. We have therefore overexpressed the genes coding for glucose 6-phosphate dehydrogenase ( g6pd ) and 6-phosphogluconate dehydrogenase ( 6pgd ) from the PPP in the oleaginous fungus Mucor circinelloides to analyze its effect on lipid accumulation. The results showed that overexpressing g6pd or 6pgd increased the lipid content of cell dry weight by 20–30% compared to the control strain, and with higher G6PD and 6PGD activities and higher mRNA levels in the overexpressing strains. The results suggest that G6PD and 6PGD are important NADPH providers and play a key role on lipid accumulation in oleaginous fungus M. circinelloides .